Adherence to Legal Culture as a Component of the Regional Industrial Enterprises’ Corporate Innovation Management while Ensuring their Sustainable Development - Klius, Yuliia; Kotova, Liubov; Ivchuk, Yuliia; Skupinskyi, Oleh (European Journal of Sustainable Development, 2020)
The article is to determine the role of the compliance culture as a part of the regional industrial enterprises’ corporate innovation management while ensuring their sustainable development. Any enterprise, operating in a market economy, aims to maximize profits as its main internal goal. Effective innovative development is an objective necessity for sustainable economic growth. The main goal of the innovative activity of enterprises or organizations can be designated as obtaining a certain number of innovations in the form of new products, technologies, raw materials, methods of organization and management with certain features. The formation of new and efficient innovation management systems by means of straight-line management is of great importance for industrial enterprise’s effective development management. The creation of new and efficient systems of management of innovation activity to direct it into an effective path is greatly important for effective development management of the industrial enterprise. Therefore, the innovation management corporate system creation and the study of its role in the effective development of the enterprise is extremely relevant. Keywords: legal culture, innovative activities, industrial enterprises, sustainable development